Distinct structures of interannual variations in stratosphere-to-troposphere ozone transport induced by the Tibetan Plateau thermal forcing - Q. Yang; T. Zhao; Y. Bai; K. Meng; Y. Luo; Z. Tian; X. Sun; W. Fu; K. Yang; J. Hu (Atmospheric Chemistry and Physics)
Stratosphere-to-troposphere transport (STT) is an essential natural source of tropospheric ozone. Focusing on the STT variations in late spring and early summer with frequent ozone STT over the Asian region, this study investigated the Tibetan Plateau (TP) thermal effect on the interannual STT variations with the meteorological data over 1980–2014. The distinct structures of interannual STT anomalies with the key areas of TP thermal forcing are identified through the 35-year climatological statistics. Positive anomalies of thermal forcing over the central and eastern TP exert opposing impacts on the increasing and decreasing ozone STT, respectively, along the northern and southern branches of the westerly jet around the TP. Such stronger TP thermal forcing induces anticyclonic anomalies in the upper troposphere over the TP and the surroundings, which strengthens and attenuates the northern and southern branches of the westerly jet, intensifying and weakening the westerly trough for more (fewer) tropopause folds of ozone STT over the East Asian region. Furthermore, the positive anomalies of thermal forcing over the western TP are related to the western enhancing and eastern declining STT over the Asian region. This study reveals the distinct structures of interannual variations in ozone STT induced by the TP thermal forcing, providing a new perspective for the TP effect on the atmospheric environment.